(untitled) (African Journal of Biomedical Research, 2019)
Buchholzia coriacea seeds have been reported to induce reproductive toxicity. In this study, the possible mechanism(s) by which these seeds induce male reproductive toxicity were examined. Methanol fraction (MFBC-50 and 100 mg/kg), hexane fraction (HFBC-50 mg/kg) or ethylacetate fraction (EFBC-50 mg/kg) of B. coriacea seeds were administered daily (p.o) for 6 weeks to rats and thereafter sacrificed. Sperm profile was examined microscopically while sex hormones were assayed using ELISA technique. Oxidative stress biomarkers were assayed spectrophotometrically in serum and testis. All treatment significantly decreased sperm motility and sperm count while sperm with defective morphology increased when compared with control. The MFBC (50 mg/kg) decreased luteinizing hormone (LH) and follicle stimulating hormone (FSH). The HFBC decreased testosterone, LH and FSH while EFBC decreased testosterone and FSH. Serum and testicular malondialdehyde (MDA) increased while serum and testicular superoxide (SOD), and testicular catalase decreased in HFBC and EFBC groups. MFBC (100 mg/kg) decreased serum SOD, testicular SOD and testicular catalase. Marked derangement of the testicular epithelium was observed in treated rats. Buchholzia coriacea seeds mediate male reproductive toxicity by precipitation of oxidative stress and suppression of the pituitary-testicular axis.